Speech-language therapy and occupational therapy for patients with mild cognitive impairment and dementia: a retrospective cohort study using German health claims data - Fiona Dörr; Daniela Holle; Bashar Morouj; Dominik Obermüller; Sascha Sommer; Markus Wübbeler; Kerstin Bilda (BMC Health Services Research)
Abstract Background Dementia is a complex, multifactorial syndrome characterised by cognitive decline and impaired daily functioning, representing a major risk factor for long-term care dependency. As the prevalence of dementia will increase due to demographic change, healthcare systems face growing challenges, including timely diagnosis, equitable access to care, and managing the rising demand for health services. Speech-language therapy (SLT) and occupational therapy (OT) can help maintain cognitive function and quality of life, particularly in the early stages of dementia or mild cognitive impairment (MCI). However, their utilisation in Germany remains poorly understood. Objective This study evaluates the utilisation and prescription patterns of SLT and OT among people with dementia or MCI and explores factors associated with therapy use, based on German claims data. Methods A retrospective cohort study was conducted using routinely collected data from the research database of the Institute for Applied Health Research Berlin (InGef), including anonymised health records of 5 million individuals in Germany. The dataset covered the period from 2017 to 2022. Incident cases of dementia or MCI were tracked for two years following diagnosis to assess therapy use and prescription patterns. Different facets associated with therapy use were analysed using multivariable logistic regression. Results A total of 63,496 individuals (58% female, 42% male) were included (81.8% with dementia, 18.2% with MCI). Of these, 4.2% received SLT and 10.3% received OT (at least one prescription within the two-year follow-up period). Male sex (Odds Ratio [OR] 1.24, 95% confidence interval [CI] 1.09–1.40) and certain dementia types were significantly associated with higher odds of receiving SLT compared to individuals with Alzheimer’s disease (AD): dementia classified elsewhere (OR 3.34, 95% CI 2.46–4.53), vascular dementia (OR 1.71, 95% CI: 1.36–2.15), and MCI (OR 1.61, 95% CI: 1.28–2.03). In contrast, these dementia types were associated with lower odds of receiving OT. Older age was negatively associated with SLT use, whereas no consistent age-related pattern was observed for OT utilisation. Conclusion Our findings reveal low utilisation of SLT and OT, highlighting significant gaps in allied health service provision for people with dementia or MCI. These results underscore the need for improved referral pathways and targeted strategies to better integrate allied health professionals into routine dementia care. Trial registration The study was not registered.